2007
DOI: 10.1016/j.solener.2007.01.015
|View full text |Cite
|
Sign up to set email alerts
|

Quantum dot containing nanocomposite thin films for photoluminescent solar concentrators

Abstract: Silicon oxide films containing CdS quantum dots have been deposited on glass substrates by a sol-gel dip-coating process. Hereby the CdS nanocrystals are grown during the thermal annealing step following the dip-coating procedure. Total hemispherical transmittance and reflectance measurements were carried out by means of a spectrophotometer coupled to an integrating sphere. For CdS-rich films, an absorption edge at photon energies in the vicinity of the band gap value of bulk CdS is observed. For lower CdS con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(41 citation statements)
references
References 41 publications
2
39
0
Order By: Relevance
“…By increasing the annealing temperature of CdS quantum dots in silicon dioxide films, the photoluminescence spectra red shifted, attributed to an increasing CdS dot cluster size. [140] These results were supported by calculations and direct X-ray diffraction (XRD) measurements of the QDs, determining that the cluster size grew at increased annealing temperature. [139] Schuler also showed that CdS-rich siliconoxide layers show an absorption band close to the bandgap of bulk CdS, while low concentration layers had bandgaps of higher energy, corresponding to finitewell and tight-bonding calculations.…”
Section: Quantum Dotsmentioning
confidence: 75%
See 1 more Smart Citation
“…By increasing the annealing temperature of CdS quantum dots in silicon dioxide films, the photoluminescence spectra red shifted, attributed to an increasing CdS dot cluster size. [140] These results were supported by calculations and direct X-ray diffraction (XRD) measurements of the QDs, determining that the cluster size grew at increased annealing temperature. [139] Schuler also showed that CdS-rich siliconoxide layers show an absorption band close to the bandgap of bulk CdS, while low concentration layers had bandgaps of higher energy, corresponding to finitewell and tight-bonding calculations.…”
Section: Quantum Dotsmentioning
confidence: 75%
“…[91] The emission spectra of the QDs used in these experiments demonstrated that increased pathlength of the emitted light through the waveguide resulted in a shape change, with the short wavelength peak decreasing with respect to the longer wavelength peak, demonstrating that re-absorption still plays an important role in these QD concentrators. [91,140] QD-based concentrators have been compared directly with organic dye containing LSC via both modeling and experimental studies. One such work compared CdSe/ZnS QD and Lumogen Red F 300 containing concentrators.…”
Section: Quantum Dotsmentioning
confidence: 99%
“…Nevertheless, organic ligands are necessary at least for colloidal QDs. Often studied and/or relevant semiconducting nanocrystals consist, for example, of CdS, CdSe, CdSe/ZnS, CdTe, InP, Si, PbS, PbSe, CuInS 2 , CuInSe 2 , with some types being commercially available; an example for multishell QDs are nanoparticles consisting of a CdSe core surrounded by successive CdS, Cd0.5Zn0.5S, and ZnS shells [20,21,96,99,[104][105][106][107][108].…”
Section: Luminescent Nanocrystalline Quantum Dotsmentioning
confidence: 99%
“…Schüler et al [20] proposed to make LSCs by coating transparent glass substrates with QD-containing composite films, using a potentially cheap sol-gel method. They reported on the successful fabrication of thin silicon oxide films that contain CdS QDs using a sol-gel dip-coating process, whereby the 1-2 nm sized CdS QDs are formed during thermal treatment after dip-coating.…”
Section: State-of-the-art Devicesmentioning
confidence: 99%